AJSS 2019
DOI: 10.34091/ajss.12.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Momentum Effect in Stock Market: Empirical Evidence from Pakistan Stock Exchange

Abstract: This study aims to examine the momentum effect presence in selected stocks of Pakistan stock market using data from Jan 2007 to Dec 2016. This study constructed the strategies includes docile, equal weighted and full rebalancing techniques. Data was extracted from the PSX – 100 index ranging from 2007 to 2016. STATA coding ASM software was used for calculating momentum portfolios, finally top 25 stocks were considered as a winner stocks and bottom 25 stocks were taken as a loser stocks. In conclusion, the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The results of four factors model of this study showed that the momentum factor could predict returns of the mutual fund industry. The results are consistent with the previous studies of Jagdesh and Titman (1993), Anjun, Ijaz and Ahmed (2016), Khan (2016) and Rasheed, Saood, Alam (2019). This study also shows consistent results with that of Detzel and Weigand (1998), Otten and Dennis (1999), Kothari andWarmer (2001), Wermers (2003), which suggested momentum factor explains the variation of the returns of the mutual funds whereas the results of this study negates the results of Yi and He (2016) that suggest that momentum factor does not capture the fund returns.…”
Section: Discussionsupporting
confidence: 93%
“…The results of four factors model of this study showed that the momentum factor could predict returns of the mutual fund industry. The results are consistent with the previous studies of Jagdesh and Titman (1993), Anjun, Ijaz and Ahmed (2016), Khan (2016) and Rasheed, Saood, Alam (2019). This study also shows consistent results with that of Detzel and Weigand (1998), Otten and Dennis (1999), Kothari andWarmer (2001), Wermers (2003), which suggested momentum factor explains the variation of the returns of the mutual funds whereas the results of this study negates the results of Yi and He (2016) that suggest that momentum factor does not capture the fund returns.…”
Section: Discussionsupporting
confidence: 93%
“…The findings show that loss aversion and overconfidence are significant predictors of investment decisions and investment performance of equity investors. Parveen and Siddiqui (2018) clarify the mechanism by which disposition effect, anchoring and overconfidence influence the investment return. The results show that anchoring and disposition effect has a positive effect on investment return and overconfidence has a negative influence on the investment returns.…”
Section: Cognitive Heuristic-driven Biases Investment Decision-making...mentioning
confidence: 88%
“…Anchoring is also considered the inability of investors to adopt new information that may divert their minds from the initial belief. Parveen and Siddiqui (2018) examined the impact of various behavioral biases in financial decision-making process of retail investors in Pakistan Stock Exchange. The researcher explored different biases that increase the irrationality in the market and compromise the perfect market hypothesis.…”
Section: Behavioral Biases and Financial Decisionsmentioning
confidence: 99%
“…Study found that cultural factors do not significantly influence decision-making process of investors. Parveen and Siddiqui (2018) examined impact of various behavioral biases in financial decision-making process of the retail investors in Pakistan Stock Exchange and explored different biases that increase irrationality in market and compromise perfect market hypothesis. A survey of Lee, Switzer, and Wang (2019) found very interesting results that investors usually prefer to invest in those stocks that belong to the local culture or are near to the indigenous cultural norms.…”
Section: Social and Cultural Factors With Investment Decision Makingmentioning
confidence: 99%